Implementation Knowledge Management for Knowing the Factors That Have Influenced Income for Traditional Retail - Dien Novita; Ermatita (Proceeding of International Conference on Science, Health, And Technology, 2021)
The massive expansion of modern retail such as minimarkets in Palembang City has recently been rampant. The existence of modern retail is now having an impact on traditional retail that has existed before. Many traditional retailers cannot compete with the modern retailers that have grown up around them. From these facts, various studies have been carried out and various solutions have been provided so that the existence of traditional retailers cannot be replaced by modern retailers. There are still many traditional retailers that still survive in this condition. This is interesting to research, especially regarding the factors that affect the income of traditional retailers so that they can survive in selling goods that are actually the same as goods sold in the nearest minimarket. In this study, the concept of knowledge management is used in identifying, creating, explaining, and distributing knowledge for use and re-study by traditional retailers to be able to compete. In this concept, the Nonaka and Takeuchi model of the externalization dimension of knowledge is used, namely the transformation of knowledge from a tacit form to an explicit form. With externalization, tacit knowledge is obtained directly from 32 traditional retailers in Palembang, namely the factors that affect income. The results showed that the dominant factors were two factors, namely the length of the business opening hour and the percentage of product availability desired by the customer. The coefficient of determination is 81.95%, this factor contributes to the income of traditional retail businesses. These results can be disseminated and communicated to other retail business owners so that it becomes a concern in formulating future business strategies.